Strategi Pengembangan Usaha Keripik Tempe (Studi Kasus: Keripik Tempe Ziyaada di Desa Sri Agung Kecamatan Batang Asam Kabupaten Tanjung Jabung Barat) - Ria Syafrianti; Nida Kemala; Siti Abir Wulandari (Universitas Batangahari Jambi, 2026)
The purpose of this study is to describe the production process, analyze internal and external conditions, determine suitable development strategies, and identify priority strategies for the Ziyaada tempe chips business in Sri Agung village. The research method applied was a survey using SWOT and QSPM analysis. The findings reveal that the Ziyaada tempe chips business, owned by Mrs. Muslikhatin, is located on Sedap Malam Street, Sri Agung Village. Production is conducted three times a week with an output 0f 17 kg per frying process. Products are sold offline to nearby stalls and restaurants at prices of IDR 2.000, IDR 8.000, and IDR 50.000. internal strengths include to have employees, self-funded capital, reinvested profits, routine production, ability to meet demand, continuous supply of soybeans, and stable prices. Weaknesses consist of limited worker skills, traditional tools, non-premium soybeans, conventional marketing, restricted sales to nearby stalls, and relatively higher prices compared to competitors. External opportunities involve untapped market potential. Meanwhile, threats comprise unsold products despite high demand, lack of digital skills, absence of government support, and more than two competitors in the market. Strategic analysis positions the business in Quadrant VIII, indicating a Growth. Based on the QSPM matrix, the priority strategy is product innovation and cost management, which are expected to strengthen competitiveness and ensure sustainability.